1972
DOI: 10.1017/s0022112072002186
|View full text |Cite
|
Sign up to set email alerts
|

The energy balance in modulated plane Poiseuille flow

Abstract: Plane Poiseuille flow in which the pressure gradient has a small amplitude time-periodic component in addition to a constant component is considered. The velocity field close to the boundaries, arising from a small amplitude high frequency disturbance to the flow, is calculated to second order in the modulation amplitude. The energy-transfer integral for the disturbance is then calculated to the same order. It is found that, if the thickness of the disturbance shear wave relative to that of the modulation shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…We note that a complete set of dimensionless parameters for the basic flow is provided by G, R 1 and R 2 . Studies relevant to the current investigation include those of Grosch & Salwen (1968) based on numerical time integration of a Galerkin approximation to the governing equations; Herbert (1972), who employed energy methods; Hall (1975), who used perturbation methods based on Floquet theory and von Kerczek (1982), where numerical techniques also based on Floquet theory were implemented. These authors looked at the stability of oscillatory plane Poiseuille flow from the standpoint that the oscillatory component could be thought of as a perturbation of the underlying steady flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that a complete set of dimensionless parameters for the basic flow is provided by G, R 1 and R 2 . Studies relevant to the current investigation include those of Grosch & Salwen (1968) based on numerical time integration of a Galerkin approximation to the governing equations; Herbert (1972), who employed energy methods; Hall (1975), who used perturbation methods based on Floquet theory and von Kerczek (1982), where numerical techniques also based on Floquet theory were implemented. These authors looked at the stability of oscillatory plane Poiseuille flow from the standpoint that the oscillatory component could be thought of as a perturbation of the underlying steady flow.…”
Section: Introductionmentioning
confidence: 99%
“…For relatively large values of G time-modulation appeared to have a stabilizing effect but when G is less than roughly 10 destabilization occurred. Herbert (1972) provided further qualitative information by examining the disturbance energy balance in modulated plane Poiseuille flow. He concluded that the oscillatory component of the basic flow inhibited energy transfer in some parameter regions and thus had a stabilizing effect on perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…The oscillatory velocity profile consists of Stokes layers a t the channel walls matched to an oscillating slug flow in the core of the channel. The linear stability theory of this OPP flow has been examined by Grosch & Salwen (1968), Herbert (1972) and Hall (1975). These three studies contain certain conclusions concerning the stability characteristics of this flow that are not entirely in obvious accord.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the plane Poiseuille flow with longitudinal wall oscillation is also investigated by many researchers because this flow is basically twodimensional and it seems that the analytical approach is more suitable [8][9][10][11][12]. Most general way to deal this flow is to assume as a combination of the plane Poiseuille flow with the Stokes layer.…”
Section: Introductionmentioning
confidence: 99%